MANAJEMEN PEMBESARAN LELE DUMBO Clarias sp. MELALUI INOVASI KOLAM TERPAL DI DESA PAKISAN KABUPATEN BULELENG - I Ketut Wija Negara; Dewa Ayu Angga Pebriani (Faculty of Science and Technology University Ibrahimy, 2017)
Catfish production in the province of Bali isn’t optimal, because it hasn’t itegarted ancillary factors suchcultivation; pond, hatcheries, feed alternatives, and super-intensive cultivation technology innovation. Innovation and alternative developed is the rearing ponds catfish using tarpaulin material. The purpose of this research is to create a pond tarp protype appropriate and provide information to rural communities, to be able to utilize these resources to activities with catfish Cara Budidaya Ikan Yang Baik (CBIB). The method used is through data collection, both secondary data and primary data. Secondary data is by observation of the existing pond tarp in Buleleng regency, then obtain primary data of conducting an experiment directly manufacture for pond tarpaulins, seed preparation, feeding management, harvesting and post-harvest. The results of this study found that, pond tarps are made under the soil surface using a mold lined with good soil to be used cultivation of catfish. Pond tarpaulin by using a mold of land besides the cost is very cheap, also can withstand the pressure from the edge of the pond so it is not easy to damage the pond. Management of water quality management can be easily done, because the pond tarp in this type of outlet. Conditions pond tarp after one cycle of post-harvest still reusable.